Punishment and racial segregation of schools: against racial threat and toward a racial control perspective - Irwin, Katherine (Critical criminology, 2022)
Beginning in the 1990s, scholars have been attuned to the ways that punitive frameworks within criminal justice institutions have been diffused to U.S. schools, often characterizing this trend as the "schools-to-jails" pathway and the criminalization of U.S. students. Looking at empirical trends, researchers have consistently found that schools primarily serving students of color are the most likely schools to rely on harsh, punitive practices. To explain these trends, scholars have tended to argue that these empirical findings support the racial threat perspective (Blalock 1967). We argue that racial threat theory is inadequate to fully understand racial disparities in school punishment trends. Relying on insights from critical race theory (CRT), we offer a racial control perspective that can explain racial disparities in school punishment in the U.S.